The Influence of Leadership Style on Employee Work Discipline at the Population and Civil Registration Office of Toli-Toli Regency: Pengaruh Gaya Kepemimpinan terhadap Disiplin Kerja Pegawai pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Toli-Toli - Ilham Jaya Pernama; A. Irfan Efendi; Syarifatul; Hedrat M. Nure (STIE MUJAHIDIN TOLITOLI, 2026)
This study aims to determine the influence of leadership style on employee work discipline at the Population and Civil Registration Office of Toli-toli Regency. This study uses a quantitative method with an associative descriptive approach. The data collection technique was carried out through the distribution of questionnaires to the entire population of 36 ASN employees. The data was analyzed using simple linear regression analysis, after going through validity, reliability, and classical assumptions tests. The results showed that leadership style had an effect on employee work discipline, with a significance value of p < 0.01 and a determination coefficient (R² = 0.38). This means that 38% of the variation in work discipline can be explained by leadership style.